Inovasi di Sektor Publik - Fransisca Mulyono (Centre for Public Policy and Management Studies, 2008)
Public sector innovation in current globalization era is inevitably a global phenomenon. This situation is supported by experiences of countries which try to focus themselves to achieve an innovation-driven economy to serve a better service for their 'customers' beside to occupy an important position in global rank. Several countries acknowledging innovation as of great importance in achieving competitive advantages. The perfect examples for this are China and India which are considered experiencing a rapid growth-leapfrogging- to become great powers in Asia. This paper has three major purposes. First, it tries to describe the importance of public sector innovation to raise its competitive advantage. Although innovation in public sector is a complex one, but it is not impossible to be attained. Second, to give some public dector innovation since it is applied for more than two decades in the world. Third, to describe some limitations to be confended and anticipated in order to raise the responsiveness of public sector to this global trend.Keywords: public sector, innovation